2023
DOI: 10.3390/w15183298
|View full text |Cite
|
Sign up to set email alerts
|

Dam Surface Deformation Monitoring and Analysis Based on PS-InSAR Technology: A Case Study of Xiaolangdi Reservoir Dam in China

Qun Wang,
Yufei Gao,
Tingting Gong
et al.

Abstract: The Xiaolangdi Dam is a key project for the control and development of the Yellow River. It bears the functions of flood control, controlling water and sediment in the lower reaches, ice prevention, industrial and agricultural water supply, power generation, and so on. Its safety is related to people’s life and property safety and local economic and social development. It is of great significance to carry out comprehensive and regular deformation monitoring for dams since the deformation is an important evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…It was found that fluctuations in reservoir water levels lead to changes in the PWP and the matric suction in the dam body, reducing the effective stress there; this is unfavorable to the Fs of the dam slope [37]. With the help of modern data transmission technology, dam slopes have been widely studied using field monitoring, which has yielded many useful results [38,39]. The rapid drawdown of reservoir water levels coinciding with heavy rainfall was found to be a critical situation for dam slope safety [40].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that fluctuations in reservoir water levels lead to changes in the PWP and the matric suction in the dam body, reducing the effective stress there; this is unfavorable to the Fs of the dam slope [37]. With the help of modern data transmission technology, dam slopes have been widely studied using field monitoring, which has yielded many useful results [38,39]. The rapid drawdown of reservoir water levels coinciding with heavy rainfall was found to be a critical situation for dam slope safety [40].…”
Section: Introductionmentioning
confidence: 99%